SENGKETA TATA USAHA NEGARA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 30 TAHUN 2014 - Sudarsono, Sudarsono (TANJUNGPURA LAW JOURNAL, 2017)
After the Reformation, several responsive laws were enacted, including Law Number 30 Year 2014 on Government Administration. The Government Administration Act is the legal basis for the government in carrying out governmental measures that provide legal protection for citizens for theactions of unlawful bodies / government officials. In the context of legal protection for the people through juridical control by the State Administrative Court, since the enactment of the Administrative Administration Law the competence that became the object of dispute in the State Administrative Court is wider, ie not only the Administrative Decision of the State, but also includes Government Action, Positive fictions, and testing of judgments of elements of abuse of authority. However, the extension of the competence of the State Administrative Court under the Government Administration Act has not been followed by the amendment of the State Administrative Justice Law, so in some cases there is an antinomy between the two laws. Such antinomies are aboutunderstanding the Decision of State Administration as well as about the enforcement of fictitious or negative fictitious lawsuits / requests. In the case of the subject of dispute, the provisions in the State Administrative Justice Act and the Administrative Law are relatively the same, in which thePlaintiff is a Civil Legal Entity, the Defendant is the State Administrative Agency / Officer, and the Intervention Party is a Civil Law Person . However, in the Government Administration Act there is a special case in the form of examination of the element of abuse of authority, where the Applicant isthe State Administration Officers / Officers. Against the antinomy and disharmonization between the State Administrative Justice Act as the formal law and the Government Administration Law as the material law, this paper seeks to conduct legal studies with the approach of legislation andconceptual approach, which is intended to realize harmonization and synchronization Between the two laws and regulations, so that the legal protection for the people will be realized through better handling of State Administration dispute in the State Administrative Court.